2020
DOI: 10.3390/polym12112488
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Composition on the Crystallization, Water Absorption, and Biodegradation of Poly(ε-caprolactam-co-ε-caprolactone) Copolymers

Abstract: Poly(ester amide)s have aroused extensive research interest due to the combination of the degradability of polyester and the higher mechanical properties of polyamide. In this work, a series of poly(ε-caprolactam-co-ε-caprolactone) (P(CLA-co-CLO)) copolymers with different compositions were synthesized by anionic copolymerization. The structure, crystallization behavior, water absorption, and biodegradation behavior of these copolymers were investigated by means of nuclear magnetic resonance (NMR), Fourier tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The water uptake of polyamides can further be influenced by the crystallinity of the polymer. It was shown that increasing the crystallinity of PA 6 by tempering resulted in a 30% reduction of the water uptake . The influence of crystallinity can be neglected, though, as the synthesized polyamides all have a similar crystallinity of approximately 50%.…”
Section: Resultsmentioning
confidence: 99%
“…The water uptake of polyamides can further be influenced by the crystallinity of the polymer. It was shown that increasing the crystallinity of PA 6 by tempering resulted in a 30% reduction of the water uptake . The influence of crystallinity can be neglected, though, as the synthesized polyamides all have a similar crystallinity of approximately 50%.…”
Section: Resultsmentioning
confidence: 99%
“…PEAs are widely used in the biomedical field and in elastomers. 17,19,20 On the other hand, PEAs obtained through ring-opening copolymerization offer a great potential in engineering plastics, [21][22][23][24][25] which can be regarded as modification of polyamides and polyesters.…”
Section: Introductionmentioning
confidence: 99%
“…As the classic representatives of polyamides and polyesters, polycaprolactam (polyamide 6, nylon 6), with higher thermal stability and good mechanical properties, [25][26][27][28][29] and polycaprolactone (PCL), with excellent biodegradability, [30][31][32][33][34] are indispensable for industry and everyday life. Thus, the synthesis of poly(ε-caprolactone-coε-caprolactam) has attracted great attention.…”
Section: Introductionmentioning
confidence: 99%